Analysis of EFL Student’s Pronunciation Errors: A Case Study of Two Adolescent Students - Muhammad Suhil; Mahruji Robiatu Romadoni (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
This study purposes to analyze students’ pronunciation errors and investigate the source of interlanguage errors on pronunciation based on theree IL aspects; social, discourse and phsycholinguistic. The participant of this research were two adolescent students who have been studied English several years. The researcher used qualitative method and collect the data with recorder and questioniarre. The result of this research showed that; first, pronunciation errors is one of the crucial problem that always discovered when EFL students speak English. Commonly, students always made an pronunciation errors in producing vowel like /æ/ and /ɪ/ sounds. Second, social, discourse, and phsycolinguistic aspect did not support their abilitiy in improving their speaking skill particularly pronunciation.